2020
DOI: 10.1631/jzus.b1900329
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PTPRR and JAG1 as key genes in castration-resistant prostate cancer by integrated bioinformatics methods

Abstract: To identify novel genes in castration-resistant prostate cancer (CRPC), we downloaded three microarray datasets containing CRPC and primary prostate cancer in Gene Expression Omnibus (GEO). R packages affy and limma were performed to identify differentially expressed genes (DEGs) between primary prostate cancer and CRPC. After that, we performed functional enrichment analysis including gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway. In addition, protein-protein interaction (PPI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Significantly upregulated genes include PLAU (urokinase-type plasminogen activator) and its inhibitor, PAI1 (plasminogen activator inhibitor 1), AKT3, PRKN, and DUSP13 ( Figure 2 C). All of these genes have been implicated in cancer progression and metastasis, their overexpression generally resulting in more aggressive phenotypes [ 35 , 36 , 37 , 38 ] and apoptosis [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly upregulated genes include PLAU (urokinase-type plasminogen activator) and its inhibitor, PAI1 (plasminogen activator inhibitor 1), AKT3, PRKN, and DUSP13 ( Figure 2 C). All of these genes have been implicated in cancer progression and metastasis, their overexpression generally resulting in more aggressive phenotypes [ 35 , 36 , 37 , 38 ] and apoptosis [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The glucose transporter SLC2A1 and other members of the protein family (Figures 2C and 3 and Supplementary Table S2) were strongly downregulated in the Tks4 Significantly upregulated genes include PLAU (urokinase-type plasminogen activator) and its inhibitor, PAI1 (plasminogen activator inhibitor 1), AKT3, PRKN, and DUSP13 (Figure 2C). All of these genes have been implicated in cancer progression and metastasis, their overexpression generally resulting in more aggressive phenotypes [35][36][37][38] and apoptosis [39].…”
Section: Changes In Mrna Levelsmentioning
confidence: 99%
“…In this study, by combining the PTP substrate-trapping strategy with immunoprecipitation, we identified PTPRR as the tyrosine phosphatases responsible for dephosphorylating MuSK. PTPRR is a subfamily of classical PTPs and is considered as a tumor suppressor regulating proliferation or differentiation of cancer cells including oral squamous cell carcinoma, cervical cancer, breast tumor, and colorectal carcinomas [27][28][29][30]. We identified Tyr754 as the possible site of MuSK dephosphorylation by PTPRR through generating Tyr to Phe triple mutations for the C-terminal residues 553/750/755 of MuSK.…”
Section: Discussionmentioning
confidence: 99%
“…GSE3325, GSE46602, GSE69223 and GSE104749 gene expression profiles have been normalized and transformed into suitable matrix using Robust Multichip Average (RMA) included in affy package of R software (version 3.6.1) consisting of background adjustment, quantile normalization and summarization pre-processing [ 6 , 18 ]. Limma package was used to identify DEGs between primary prostate cancer and noncancerous prostate samples.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the combined score represented intermolecular interactions and the protein pairs with combined score > 0.4 were selected to construct the PPI network [ 21 ]. Nodes were drawn in different sizes and colors, which represented the node degree and the regulation (up or down), respectively [ 18 ]. The hub genes were calculated by different methods with cytohubba [ 22 ].…”
Section: Methodsmentioning
confidence: 99%